2006
DOI: 10.1021/ma0613178
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Cylindrical Brushes in Solution:  Effect of Side Chain Length

Abstract: The conformation of cylindrical brush polymers with a polymethacrylate main and polystyrene side chains (6 e P n sc e 33, with P n sc the number-average degree of polymerization of the side chains) were studied by combined light and small-angle neutron scattering experiments. The results reveal that the main chain stiffness expressed in terms of the Kuhn statistical segment length, l k , increases with side chain length but does not follow scaling predictions which most probably is due to the limited length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
284
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(319 citation statements)
references
References 59 publications
31
284
3
1
Order By: Relevance
“…Such polymers are widely termed 2 "cylindrical molecular brushes" due to their steric-induced stiffness and axes of symmetry. [39][40][41][42][43] These cylindrical brushes can be modeled as wormlike chains with the same average crosssectional radius (Rc) along the entire backbone. 5,[44][45][46] On the other hand, if the macromonomer and diluent copolymerize at different rates, the resulting gradient sequences are anticipated to template different side chain conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Such polymers are widely termed 2 "cylindrical molecular brushes" due to their steric-induced stiffness and axes of symmetry. [39][40][41][42][43] These cylindrical brushes can be modeled as wormlike chains with the same average crosssectional radius (Rc) along the entire backbone. 5,[44][45][46] On the other hand, if the macromonomer and diluent copolymerize at different rates, the resulting gradient sequences are anticipated to template different side chain conformations.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent SANS investigations on the conformation of polystyrene-grafted polymethacrylate show a flexible coil to stiff cylinder transition as the length of the side chains increases. 5 OEG-grafted polymers are promising materials for different applications owing to the special properties of EG in addition to the comblike architecture, which allows independent variation of the length and composition of the backbone and side chains to achieve desired structures and functions. A main research activity involves optimization of the properties of OEG-grafted polymers as polymer electrolytes where the OEG side chains are good ionic conductors.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those observed for PS-MA PM in toluene and cyclohexane. 17,19 The unperturbed mean-square radius of gyration, /S 2 S 0 , for wormlike chains with a contour length L is expressed as 20…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] We have studied PM consisting of a PS main chain and PS side chains with a benzyl group at each end (benzyl-PS PM) and showed that its A 2 in cyclohexane vanishes at 34.5 1C, which is identical to the Y temperature of linear PS in cyclohexane. [13][14][15][16] In contrast, the values of A 2 for PM consisting of a polymethacrylate main chain and PS side chains with a butyl group at each end (PS-MA PM) in d 12 -cyclohexane were shown to be positive at 20 1C, 17 far below the Y temperature (40 1C) of linear PS in d 12 -cyclohexane. Although the butyl end in PS-MA PM may be a primary cause of the positive A 2 , there may be a possible effect on the A 2 of the polymethacrylate main chain.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation